Water resources environmental planning, management, and development - Biswas, Asit K. (McGraw-Hill, 1997)
Offers water resource and environmental professionals international coverage of water quality management and environmental issues, including the environmental impact of water development. This book presents concepts and data on waterlogging and salinity, sedimentation, land use, eutrophication, fisheries, and aquatic weeds.